Kekuatan Mengikat Surat Penunjukan Penyedia Barang dan Jasa Pemerintah dalam Kontrak Pengadaan Barang/Jasa Pemerintah di Masa Pandemi Covid-19 - Merry Tjoanda (SASI, 2020)
The process of determining the auction winner for a goods / services procurement project ends with the issuance of SPPBJ by PPK. The purpose of this study is to analyze the legally binding force of the Goods / Services Provider Appointment Letter (SPPBJ) in government procurement contracts of goods / services, especially during the Covid-19 pandemic. The results showed that before the contract for the procurement of goods / services was signed by the PPK and the provision of goods / services, the SPPBJ that had been issued by the function of executing the auctioned work provided that there were no objections from other participants and the rebuttal period had ended. SPPBJ acts as a binding contract, where SPPBJ is very much needed because the contract may be canceled or transferred due to refocusing of activities and relocation of budgets due to the impact of the Covid-19 pandemic as it is today. There needs to be a more stringent regulation in the SPPBJ issuance process to deal with irregularities that may still occur, which is carried out by PPK.